2022
DOI: 10.1021/acs.orglett.2c03823
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Decarbonylative Reductive Alkylation of Aroyl Fluorides with Alkyl Bromides

Abstract: This paper describes the nickel-catalyzed reductive alkylation of aroyl fluorides with alkyl bromides in a decarbonylative manner. In this reaction, various functional groups are well tolerated and the C(sp 2 )−C(sp 3 ) bond can be constructed directly without the use of organometallic reagents. The present reaction is a cross-electrophile coupling via the radical pathway, affording the corresponding alkylarenes in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…The compatibility of aryl halides in similar catalytic cycles is known, often as part of a cross-coupling reaction resulting in the formation of sp 2 C-sp 3 C bonds. [58][59][60] To learn if aryl halides would compete with the polystyryl chains and participate in the catalytic cycle, reactions were carried out in the presence of several aryl bromides. As shown in Trials 19-21, similarly high yields of polymer coupling were observed even in the stoichiometric presence of 4,4 0dibromopnenyl (DBP), 9,10-dibromoanthracene (DBA), or 9-bromoanthracene (9-BA), indicating the strong preference for the PS chains over the arenes in terms of the nickel catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The compatibility of aryl halides in similar catalytic cycles is known, often as part of a cross‐coupling reaction resulting in the formation of sp 2 C‐sp 3 C bonds 58–60 . To learn if aryl halides would compete with the polystyryl chains and participate in the catalytic cycle, reactions were carried out in the presence of several aryl bromides.…”
Section: Resultsmentioning
confidence: 99%
“…Acyl fluorides (RFC=O) are versatile reagents in organic synthesis and exhibit three types of reactivity to produce valuable products (Scheme a). Acyl fluorides are traditionally used as acylating agents (RC=O sources), wherein they react with nucleophiles such as alcohols, amines, and thiols to form esters, amides, and thioesters, respectively. Compared to other acylating agents such as acid chlorides or anhydrides, acyl fluorides are less prone to hydrolysis and other side reactions. Furthermore, acyl fluorides have recently been used as “R” source for transition-metal-catalyzed decarbonylative cross-coupling reactions. Acyl fluorides can also be used as the “F” source in fluorination reactions to synthesize diverse fluorinated compounds that have applications in the pharmaceutical industry, materials engineering, , and agrochemical development. The appropriate balance of stability and reactivity of acyl fluorides toward water, protic solvents, and transition metal catalysts makes them valuable reagents in organic synthesis. …”
Section: Introductionmentioning
confidence: 99%